2021
DOI: 10.3390/molecules26041019
|View full text |Cite
|
Sign up to set email alerts
|

Trichilianones A-D, Novel Cyclopropane-Type Limonoids from Trichilia adolfi

Abstract: The fractionation of an ethanol extract of the bark of Trichilia adolfi yielded four novel limonoids (trichilinones A-D, 1-4), with five fused rings and related to the hortiolide-type limonoids. Starting with an ε-lactone, which is α,β-unsaturated in trichilinones A and D (1 and 4), attached to a tetrahydrofuran ring that is connected to an unusual bicyclo [5.1.0] hexane system, joined with a cyclopentanone with a 3-furanyl substituent [(2-oxo)-furan-(5H)-3-yl in trichilinone D (4)], the four compounds isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…This information suggested the existence of a ternary ring among C-1/5/10 in 1 . The key HMBC correlations (Figure ) from H-1 (δ H 1.24) to C-5, C-10, and keto-carbon (C-6, δc 203.0), from Me-19 (δ H 1.40) to C-1, C-5, and C-10, and from H-7 (δ H 5.19) to C-5 and C-6, still lacking one degree of unsaturation, suggested that a novel ternary carbon ring was formed , by the C-1-C-5 carbon–carbon bond. The perfect 1 J CH -resolved HSQC spectrum (Figure S1) of 1 showed that the one-bond proton-carbon coupling constant of H-1 ( 1 J CH 167.4 Hz) was obviously different from that of H-9 ( 1 J CH 117.1 Hz) of cyclohexane, while it was similar to the reported proton of cyclopropane ( 1 J CH 161.0 Hz), , which confirmed the existence of the cyclopropane ring in 1 .…”
Section: Results and Discussionmentioning
confidence: 71%
“…This information suggested the existence of a ternary ring among C-1/5/10 in 1 . The key HMBC correlations (Figure ) from H-1 (δ H 1.24) to C-5, C-10, and keto-carbon (C-6, δc 203.0), from Me-19 (δ H 1.40) to C-1, C-5, and C-10, and from H-7 (δ H 5.19) to C-5 and C-6, still lacking one degree of unsaturation, suggested that a novel ternary carbon ring was formed , by the C-1-C-5 carbon–carbon bond. The perfect 1 J CH -resolved HSQC spectrum (Figure S1) of 1 showed that the one-bond proton-carbon coupling constant of H-1 ( 1 J CH 167.4 Hz) was obviously different from that of H-9 ( 1 J CH 117.1 Hz) of cyclohexane, while it was similar to the reported proton of cyclopropane ( 1 J CH 161.0 Hz), , which confirmed the existence of the cyclopropane ring in 1 .…”
Section: Results and Discussionmentioning
confidence: 71%
“…In addition, the 1D NMR data indicate the presence of one methoxy group, five oxygenated but saturated carbons, four non-protonated but saturated carbons, eight saturated CH-groups (of which three are oxygenated), three saturated methylene groups and nine methyl groups. The atom numbering used in this study (see Figure 2 ) follows the same system as in our previous work [ 21 ], which is based on an earlier study of hortiolide-type limonoids isolated from Hortia colombiana [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…14-H and 16-H 2 give HMBC correlations to the keto function, while 14-H in addition gives correlations to C-8, C-12, C-13, C-17 and C-18, which show the position and nature of C-15 and close the second ring. The missing substituent on C-17 is a 3-furanyl group, and this partial structure was determined in the same way as with the trichilianones [ 21 ] by COSY, HMBC and 1 J (C,H) couplings constants. This forms the third ring accounting by itself for three unsaturations, and the NMR data are quite similar to those reported for other limonoids containing a 3-furanyl substituent [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations